Conversational implicature in interviews with Malaysian transwomen / Khairunnisha Redzzuan - Khairunnisha , Redzzuan (2019)
Stigma and discrimination against transgender (also known as transphobia) has become prevalent in Malaysia over the years. A common problem faced by transgender is accessibility to healthcare and many have experienced deliberate discrimination (Lombardi 2009). Discussing healthcare issues for Malaysian transgenders is considered a sensitive topic as the topic requires them to discuss their identity as well as many health related matters which are usually not similar to what the general public are facing. Thus, based on the Paul Grice’s Cooperative Principle and maxims, this study aims to investigate the notion of implicatures to help uncover how transphobia becomes a factor in influencing healthcare access for this community. The data is based on narrative interviews of nine transwomen, working in various places in urban Kuala Lumpur. Findings reveal that the participants observed and not observed all of the maxims in the interviews. The participants employed several strategies to flout the maxims such as ‘hedging’, ‘circumlocution’, ‘evasion’ dan ‘ignoring the question’. Further, the findings also reveal that the adjacency pair of question and answer can influence the participants to observe and not observe maxims. The findings of the study will benefit the general public to understand the predicaments that the transgenders in Malaysia are facing in terms of healthcare access. Also, it will help people to understand that the adjacency pair of question and answer can become a factor to motivate people to observe and not observe maxims in conversations.